2004
DOI: 10.1007/s00424-003-1201-1
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and a functional implication of Ca 2+ -activated K + current in mouse aortic endothelial cells

Abstract: We employed the patch-clamp technique to investigate a Ca(2+)-activated K(+) (K(Ca)) current in cultured mouse aortic endothelial cells (MAECs). In the whole-cell mode, an increase in cytosolic [Ca(2+)] ([Ca(2+)](i)) to 2 micro M activated an outwards current. The [K(+)](o)-dependent change of the reversal potentials agreed well with the predicted Nernstian relation, suggesting that it was a K(Ca) current. The Hill coefficient (4) and EC(50) (740 nM) were obtained from the current/[Ca(2+)](i) relationship. Ibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…1). 1 Collectively, these data are consistent with the rather lowaffinity block by external TEA of both native and recombinant IK Ca channels (IC 50 value: 8 -10 mmol/l) (2,27,35) along with the SK Ca 2 and SK Ca 3 channel isoforms detected in the vascular endothelium (IC 50 values: ϳ3 and ϳ9 mmol/l, respectively) (4,43). Similar to TEA, we also observed that evoked NO production was unaltered in the presence of 50 mol/l BaCl 2 and 100 mol/l ouabain, which block inwardly rectifying K ϩ (Kir) channels (23) and Na ϩ -K ϩ -ATPase (29), respectively (Fig.…”
Section: Resultssupporting
confidence: 84%
“…1). 1 Collectively, these data are consistent with the rather lowaffinity block by external TEA of both native and recombinant IK Ca channels (IC 50 value: 8 -10 mmol/l) (2,27,35) along with the SK Ca 2 and SK Ca 3 channel isoforms detected in the vascular endothelium (IC 50 values: ϳ3 and ϳ9 mmol/l, respectively) (4,43). Similar to TEA, we also observed that evoked NO production was unaltered in the presence of 50 mol/l BaCl 2 and 100 mol/l ouabain, which block inwardly rectifying K ϩ (Kir) channels (23) and Na ϩ -K ϩ -ATPase (29), respectively (Fig.…”
Section: Resultssupporting
confidence: 84%
“…As shown in Figure 2a, clotrimazole, an inhibitor of IKCa1 channels (Wang et al, 2003;Ahn et al, 2004;Mork et al, 2005), significantly decreased HEC-1-A cell numbers, as manifested by the right shift of the growth curve. Further, HEC-1-A cell proliferation was suppressed by clotrimazole in a dose-dependent manner (Figure 2b).…”
Section: Increased Expression Of Ikca1 In Ecmentioning
confidence: 84%
“…Equations A1-A3 were fitted to rat mesenteric EC Kir currentvoltage (I-V) data in the Ϫ100 to ϩ40 mV range ( Fig. 2A, solid (9,10), mouse aortic endothelial cells (MAECs) (2), and Xenopus oocytes (81). Whole cell I-V experimental data (10) were rescaled using capacitance values from source cells and rat mesenteric ECs (assumed to be 14 pF) and fitted using the linear K Ca current equations (Fig.…”
Section: Membrane Electrophysiologymentioning
confidence: 99%